Historia a Debate, Tendencia historiografica latina y global - Barros, Carlos (2005)
In this text is explained shorty the formation in these past years of Historia a Debate as academmic tendency and their news characteristics: Latin and transatlantic, digital and global. Complementary phenomenon of the well-known reflection fórum and it debates historiographer, born in Santiago of Compostela in 1993. Both interralated processes and unpublished, just like internationally as in the history of our respective national historiographies, that we locates to the vanguard of the use os the frontier technologies for the generation of a new one global academic sociability